HISTORY OF THE MOSQUES OF NORTHERN USTYURT (DONYZTAU) (IN THE MID-19TH AND EARLY 20TH CENTURIES) (Journal of history, 2026)
Abstract. Introduction. This article examines the current state of research on religious residential complexes (including a mosque, school, and residential buildings) built in the 19th and 20th centuries in Donistau (Northern Ustyurt), a region of the Aral-Caspian region, and focuses on the history of the monuments' construction. Purpose of the study. During the Soviet period, the spread of Islam in the region, the study of the region's mosques, and the lives and activities of religious figures were not among the most relevant topics in the historiography of Kazakhstan's history. In this regard, our main goal will be a scientific assessment of the information preserved in folk memory and published works concerning mosques and religious residential complexes, which are the embodiment of the spiritual culture of our region, rich in “blank spots.” Methodology of the work. Throughout the article, historical methodology methods for describing, analyzing, and comparing monuments are widely presented. Results of the study. The characteristics of the region's mosques and madrassas are highlighted and described. Attention is paid to religious and residential complexes as part of our "cultural heritage," and an attempt is made to determine their origins. Scope of application of the results. The information presented in this publication is useful for ethnologists, cultural scientists, historians, and the general readership interested in learning about the history of the Kazakh people. Research findings. By studying the mosques and madrassas built in the region as our tangible cultural heritage, we identified a spiritual connection with neighboring fraternal peoples, based on the moral life and service of the people who built these mosques and the religious figures who taught in the madrassas.
Keywords: Islam; Northern Ustyurt; mosque; religious-residential complex